EFFECTIVE MANAGEMENT DECISIONS: METHODS AND TECHNIQUES - Світлана Бреус; Віталій Пригарський (Економіка та суспільство)
The article is devoted to the study of methods and techniques for making and managing effective managerial decisions. It is established that managerial decisions are multi-faceted and varied. Managerial decisions are classified depending on whether they require the development and/or modification of the methods and techniques for their implementation, based on the results of research by scholars. The conclusion is made about the necessity of conducting an in-depth analysis of management methods and techniques for companies to make effective decisions, considering diverse influencing factors on their activities under precedent conditions and circumstances, in the context of adapting to these and subsequently developing theoretical-methodological tools. Attention is focused on the fact that modern business faces constant challenges related to russia's full-scale war against Ukraine, deepening imbalances, and the continuation of negative trends as a result. It is concluded that, under such conditions, decision-making requires extensive application of modern methods and approaches at all levels of management, with appropriate modification and optimization of the decision-making process itself. The activities of LLC "Nova Poshta" are analyzed as a prominent representative of a business that successfully uses innovative approaches to management but must continuously improve and adapt methods and techniques to new challenges for successful market operation. It is determined that LLC "Nova Poshta" serves as an example of a successful combination of innovation and traditional approaches, which contributes and can have a significant impact on ensuring not only the company's viability during russia's full-scale war against Ukraine but also dynamic changes in the post-war market. The conclusion is drawn that effective managerial decision-making is the foundation of successful enterprise functioning.